HOME TRAINING : LABELING DAN PACKAGING UNTUK PENGUATAN UMKM KERIPIK PISANG DI BANGKO KIRI - Nasrullah, Nasrullah; Hafiz, Muhammad; Jonathan Neohansen (Komunitas Manajemen Kompetitif, 2025)
In Bangko Pusako there are many famous culinary foods, UMKM actors are interested in developing Kepok Banana Chips culinary. However, UMKM actors must face market competition and the problem is that many UMKM actors are not yet skilled in product labeling which is the key to winning market competition by attracting consumers. This study uses the PAR (Participatory Action Research) method which involves UMKM to actively participate in product labeling, starting from information, design and marketing label strategies. The results obtained are that UMKM actors are increasingly skilled and the demand for Kepok Banana Chips products is increasing in the market. The conclusion of this study, the PAR method has proven successful in facing competitors in the market and the use of labels also increases product demand and makes UMKM actors understand how to satisfy consumer desires.